The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/ajim.4700130603
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and brain cancer mortality: A preliminary study of East Texas residents

Abstract: The relationship between various occupational exposures and brain cancer was investigated in a case-control study using mortality data from 202 males who died in East Texas from gliomas in 1969-1978 and 238 male controls randomly selected from all deaths in East Texas in 1969-1978. Using the occupational classification scheme of the U.S. Bureau of the Census, the risk for brain cancer was significantly increased for male workers employed in the transportation, communication, and utilities industries [odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 25 publications
1
26
1
3
Order By: Relevance
“…An association between electrical work and brain tumors has also been reported in previous epidemiologic studies (14)(15)(16)(19)(20)(21) although negati ve results have also emerged (22,23). The Norwegian census cohort study (5) showed no exces s risk for brain tumors among electrical workers, and our findings do not support the hypothesis that exposure to electric or magnetic field s in power companies enhances the risk for brain tumor.…”
Section: Discussioncontrasting
confidence: 56%
“…An association between electrical work and brain tumors has also been reported in previous epidemiologic studies (14)(15)(16)(19)(20)(21) although negati ve results have also emerged (22,23). The Norwegian census cohort study (5) showed no exces s risk for brain tumors among electrical workers, and our findings do not support the hypothesis that exposure to electric or magnetic field s in power companies enhances the risk for brain tumor.…”
Section: Discussioncontrasting
confidence: 56%
“…The second method used a tiered assignment of exposure that has been employed in death-certificate-based case-referent studies of magnetic-field exposure and brain cancer (14,15). This approach classified people into one of four exposure categories according to a combination of occupation and industry codes.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…A case-control study ofeast Texas residents who had died of glioma found men employed in occupations involving electromagnetic field exposure to have an elevated risk (OR = 3.94, 95% CI:1.52-10.20) (41). When degree of exposure was categorized according to the scheme of Lin et …”
Section: Studies Of Brain Cancer Onlymentioning
confidence: 99%
“…Seven studies (32,(37)(38)(39)(40)(41)(42) looked specifically at risks ofbrain or nervous system cancer. All seven produced evidence of an association with electromagnetic radiation exposure in at least some occupational categories.…”
Section: Consistencymentioning
confidence: 99%